Searching for optical companions to four binary millisecond pulsars with the Gran Telescopio Canarias. Issue 2 (16th January 2020) - Kirichenko, A Yu; Karpova, A V; Zyuzin, D A; Zharikov, S V; López, E A; Shibanov, Yu A; Freire, P C C; Fonseca, E; Cabrera-Lavers, A
ABSTRACT: We report on multiband photometric observations of four binary millisecond pulsars with the Gran Telescopio Canarias. The observations led to detection of binary companions to PSRs J1630+3734, J1741+1351, and J2042+0246 in the Sloan g ′, r ′, and i ′ bands. Their magnitudes in the r ′ band are ≈24.4, 24.4, and 24.0, respectively. We also set a 3σ upper limit on the brightness of the PSR J0557+1550 companion in the r ′ band of ≈25.6 mag. Combining the optical data with the radio timing measurements and white dwarf cooling models, we show that the detected companions are cool low-mass white dwarfs with temperatures and ages in the respective ranges of (4–7) × 10 3 K and 2–5 Gyr. All the detected white dwarfs are found to likely have either pure hydrogen or mixed helium–hydrogen atmospheres.